Signed domination in Kronecker product of two complete graphs - Zhao, Yancai; Shan, Erfang; Miao, Lianying (Utilitas Mathematica, 2013)
Given two graphs G1 and G2. The Kronecker product G1 ⊗ G2 of G1 and G2 is the graph which has vertex set V(G1 ⊗ G2) = V(G1) x V(G2) and edge set (Equation). In this paper, we determine the exact value of signed domination number of Km ⊗ Kn as a main result, and provide the exact values of minus domination number and paired domination number of Km⊗Kn.